O dispensacionalismo e a utilização de símbolos judaicos nos cultos evangélicos - Maynard, Cândido Luiz Santos (2016)
The wear suffered over time, new technologies and new religious proposals are some of the challenges that evangelical, traditional, Pentecostal and neo-Pentecostal churches faces. This study aims to identify the possible reactions of the churches in the modern neo-Pentecostal, against the intervention of secularization and the role of dispensationalism in this action. After a long and rich historical process of pluralization of our religious matrix. As an instrument we made use of bibliographic research, based on proposals from authors such as Peter Berger, Ricardo Mariano and Charles C. Ryrie, and readings of Brazilian demographic data obtained from the IBGE - Brazilian Institute of Geography and Statistics. We seek to understand how neo-Pentecostal communities have sought to overcome this process, due to the little or apparent lack of symbols that bind their identity to the sacred, contrary to Catholicism that holds a "rich" symbolic capital, though losing their numerical leadership position every decade. What would be its maintenance tool of sacred symbols? We conclude that the use of symbolic capital of the Judaism is being used for this purpose. These appropriations are manifestations in response to pressures, using the dispensationalism, even unconsciously, to legitimize them institutionally.